2019
DOI: 10.1103/physrevb.99.104418
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear transport, dynamic ordering, and clustering for driven skyrmions on random pinning

Abstract: Using numerical simulations, we examine the nonlinear dynamics of skyrmions driven over random pinning. For weak pinning, the skyrmions depin elastically, retaining sixfold ordering; however, at the onset of motion there is a dip in the magnitude of the structure factor peaks due to a decrease in positional ordering, indicating that the depinning transition can be detected using the structure factor even within the elastic depinning regime. At higher drives the moving skyrmion lattice regains full ordering. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 103 publications
(190 reference statements)
0
16
0
Order By: Relevance
“…For clarity, we have normalized V ⊥ to the value of V || at high drives by dividing V ⊥ by α m /α d and multiplying it by −1. We can also characterize the dynamic phases by measuring the skyrmion velocity deviations in the x and y-directions as in previous work 100,101 Fig. 14(b) indicates that the velocity deviations are largest in the plastic flow phase, and diminish to a constant value in the moving crystal phase.…”
Section: B Intermediate and High Magnus Forcementioning
confidence: 89%
“…For clarity, we have normalized V ⊥ to the value of V || at high drives by dividing V ⊥ by α m /α d and multiplying it by −1. We can also characterize the dynamic phases by measuring the skyrmion velocity deviations in the x and y-directions as in previous work 100,101 Fig. 14(b) indicates that the velocity deviations are largest in the plastic flow phase, and diminish to a constant value in the moving crystal phase.…”
Section: B Intermediate and High Magnus Forcementioning
confidence: 89%
“…All particleparticle interactions have the same pairwise form of a modified Bessel function, F ss i = N i K 1 (r ij )r ij that falls off exponentially for large r. Here r ij = |r i −r j | is the distance between particles i and j, andr ij = (r i − r j )/r ij . This interaction potential has been used previously for particle-based models of skyrmions, and in the absence of pinning it causes the particles to form a hexagonal lattice 37,41,51,54,60 . The driving force F D = F Dx is the same for all particles.…”
Section: Simulationmentioning
confidence: 99%
“…In addition, clustering or species segregation can occur. Recent continuum and particle-based simulations of monodisperse skyrmions showed that clustering transitions can occur in samples containing strong pinning or quenched disorder 52,54 . Our results demonstrate that clustering can also occur in the absence of pinning when there is any dispersity in the skyrmions that produces differences in the Magnus term.…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions moving near the boundary of a magnetic multilayer have also been shown to repel away from the boundary [27]. Furthermore, skyrmions interacting with neighbouring skyrmions have also been shown to repel each other due to the dipole-dipole and exchange interactions, thus leading to the possibility of skyrmionskyrmion interaction [28,29] and confinement of skyrmion diameter when a layer is saturated by skyrmions [30]; the extreme case being a skyrmion crystal. Driving individual skyrmions through a disordered landscape has been extensively studied under the effects of SOT from a HM layer [5,31], spin transfer torque (STT) in the FM layer [32], and more recently ISTT [24,25].…”
Section: Introductionmentioning
confidence: 99%